PENGARUH MINAT BELAJAR DAN DISIPLIN DIRI TERHADAP PRESTASI BELAJAR BAHASA INGGRIS (SURVEI SISWA SMP NEGERI DI KOTA BEKASI) - Ruwaiza Sasmita (Universitas Indraprasta PGRI, 2018)
Abstract:This study aims to find out whether there is an interactive effect between learning interest and self-discipline on English learning achievement of student in State Junior High School in Bekasi city. To determine whether there is an effect of learning interest on English learning achievement of student in State Junior High School in Bekasi city. To determine whether there is an effect of self-discipline on English learning achievement of student in State Junior High School in Bekasi city. The research hypothesis tested includes: 1) There is a significant interactive effect between learning interest and self-discipline on the achievement of learning English. 2) There is a significant effect of learning interest on learning achievement in English. 3) There is a significant effect of self-discipline on the achievement of learning English. The study was conducted by survey method. In this study the population was secondary school students of State Junior High School in Bekasi city and 77 students was selected out of the entire population. The data were analyzed statistically using linier regression analyses. The result showed that: 1) There is a significant interactive effect between learning interest and self- discipline on English learning achievement of student in State Junior High School in Bekasi city 2) There is a significant effect of learning interest on English learning achievement of student in State Junior High School in Bekasi city. 3) There is a significant effect of self- discipline on English learning achievement of student in State Junior High School in Bekasi cityKeyword: learning interest, self-discipline, English learning achievement Abstrak:Penelitian ini bertujuan untuk mengetahui pengaruh minat belajar dan disiplin diri secara bersama-sama terhadap prestasi belajar bahasa Inggris siswa SMP Negeri di Bekasi. Untuk mengetahui pengaruh minat belajar terhadap prestasi belajar bahasa Inggris siswa SMP Negeri di Bekasi. Untuk mengetahui pengaruh disiplin diri terhadap prestasi belajar bahasa Inggris siswa SMP Negeri di Bekasi. Hipotesis penelitian yang di uji meliputi: 1) Terdapat pengaruh yang signifikan minat belajar dan disiplin diri secara bersama-sama terhadap prestasi belajar bahasa Inggris. 2) Terdapat pengaruh yang signifikan minat belajar terhadap prestasi belajar bahasa Inggris. 3) Terdapat pengaruh yang signifikan disiplin diri terhadap prestasi belajar bahasa Inggris. Penelitian dilakukan dengan metode survei. Populasi adalah siswa-siswa kelas VIII SMP negeri di kota Bekasi dengan besar sampel 77 siswa. Dengan pengujian menggunakan teknik regresi ganda. Hasil pengujian hipotesis diperoleh kesimpulan sebagai berikut: 1) Terdapat pengaruh yang signifikan minat belajar dan disiplin diri secara bersama-sama terhadap prestasi belajar bahasa Inggris siswa SMPN kota Bekasi. 2) Terdapat pengaruh yang signifikan minat belajar terhadap prestasi belajar bahasa Inggris siswa SMPN kota Bekasi. 3) Terdapat pengaruh yang signifikan disiplin diri terhadap prestasi belajar bahasa Inggris siswa SMPN kota Bekasi.Kata kunci: minat belajar, disiplin diri, prestasi belajar bahasa Inggris